The Preliminary Design Of A Nano Satellite Engineering Model For Remote Sensing Expe - Md. Said, Md. Azlin; Syed Hassan, Syed Idris; Kamal Adnan, Muhammad Shamsul; Allaudin, Mohd Faizal; Othman, Mohd Helmi; Zakaria, Kamal Azli (2003)
Nanosatellite means small satellites where the total mass are less than 10kg including the main payloads an Small satellite missions was not only driven by reduction of the space budgets but it was also made possible by of the technology and miniaturization of component. The new advancement of technology trends allow the applic sensing, communications and space science to benefit from the development of small satellites.